2020
DOI: 10.3390/cancers12102785
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Inhibition, TGF-β and EMT in Cancer

Abstract: Angiotensin inhibitors are standard drugs in cardiovascular and renal diseases that have antihypertensive and antifibrotic properties. These drugs also exert their antifibrotic effects in cancer by reducing collagen and hyaluronan deposition in the tumor stroma, thus enhancing drug delivery. Angiotensin II signaling interferes with the secretion of the cytokine TGF-β—a known driver of malignancy. TGF-β stimulates matrix production in cancer-associated fibroblasts, and thus drives desmoplasia. The effect of TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 149 publications
(211 reference statements)
1
23
0
Order By: Relevance
“…As a multifunctional cytokine, TGF-β participates in numerous cell biological processes and acts on tumour cells by autocrine and paracrine. TGF-β family is closely related to EMT [ 26 ]. In tumour progression, TGF-β can activate a series of signaling pathways, including Notch [ 27 ], Wnt [ 28 ], and Smad [ 29 ] signaling pathways, and the cross-talk of these signaling pathways play a synergistic role to start the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…As a multifunctional cytokine, TGF-β participates in numerous cell biological processes and acts on tumour cells by autocrine and paracrine. TGF-β family is closely related to EMT [ 26 ]. In tumour progression, TGF-β can activate a series of signaling pathways, including Notch [ 27 ], Wnt [ 28 ], and Smad [ 29 ] signaling pathways, and the cross-talk of these signaling pathways play a synergistic role to start the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence has demonstrated that various signaling pathway/proteins are involved in the EMT progression of numerous cancers. Pallasch and Schumacher revealed that TGF-β, a known driver of malignancy is also an inducer of EMT in various cancers ( 43 ). It is reported that diphenyl urea derivative could serve as an inhibitor on human lung cancer cell migration by disrupting EMT via Wnt/β-catenin and PI3K/Akt signaling ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adjacent cells may communicate with each other through different mechanisms. Secretion of a specific chemokine, such as TGF-β, is one of the most investigated mechanisms in tumour–stroma interaction [ 67 , 68 , 69 ] ( Table 1 ). Active molecules may be released by different cell types, and they may target several other cells.…”
Section: Discussionmentioning
confidence: 99%